Development and hydraulic performance evaluation of gravity drip system of irrigation for precision kitchen gardening - SAHU, KHOMENDRA; SINHA, JITENDRA; TRIPATHI, M. P. (Journal of Soil and Water Conservation, 2020)
Gravity drip system of irrigation is a cheap, efficient and précised way of providing irrigation water for the kitchen garden. The system is simple to develop, install, operate and very much cater to the need of urban as well as rural kitchen gardening and needs of small and marginal farmers under Badi system of cultivation. It is especially suitable for un-electrified as well as unreliable electric supply area. However, its hydraulic performance needs to be assessed before being used in the kitchen garden for smooth and precise application of water and nutrient. In this study a gravity drip system of irrigation was developed and its hydraulic performance has been evaluated. The system was developed with a platform supported by a frame of 2.55 m height, an overhead tank of 750 liter, 20 m sub main of 63 mm diameter, 200 m lateral of 16 mm with 1.3 lph rated discharge, control valve, flush valve, 10 nos. lateral filters, 10 nos. lateral valves, end caps etc. for a plot of 100 sq. m. (20m Ã— 5m). Hydraulic performance of the system was then evaluated on levelled field at Department of Soil and Water Engineering, IGKV, Raipur, in terms of effect of pressure (head) on discharge, manufacturing coefficient of variation, mean flow rate deviation, uniformity coefficient, application efficiency and distribution efficiency at the falling head of 3.55 m to 2.60 m from the emitting surface. Coefficient of variation, emitter flow variation, uniformity coefficient, application efficiency and distribution efficiency was found to be 4.77%, 14.54%, 95.23%, 91.21% and 95.97% which are in the acceptable limits.